INFLAMMATION AS A RISK FACTOR OF PRETERM DELIVERY - Ventskivska, I.B.; Zahorodnia, O.S. (World of Medicine and Biology, 2021)
Spontaneous preterm delivery remains the leading cause of neonatal mortality and morbidity, especially in gestational periods less than 28 weeks. The content and ratio of CD-4 and CD-8 lymphocytes, as well as the concentration of interleukin-1 and interleukin-10 in the blood serum, were studied in 90 women with premature labour at 24–28 weeks and in 91 women with preterm delivery at 28–34 weeks. The control group consisted of 32 pregnant women with an uncomplicated course of pregnancy. It has been shown that in women with preterm labour at 28–34 weeks, the number of T-helpers and the concentration of pro-inflammatory cytokines was significantly higher than in healthy pregnant women. The CD-4/CD-8 index in both groups of preterm delivery was high at 1.2, while in healthy pregnant women, it was 0.8. The identified differences justify the development of treatment tactics in different gestational terms.
Keywords: preterm delivery; interleukin-1; interleukin-10; T-helpers; T-suppressors